Community Involvement in Public Activities as a Manifestation of Active and Responsible Citizenship - Riskawati Riskawati; Akbar Aba; Hendri Irawan (Indonesian Journal of Civic and Law Studies (IJCL), 2025)
Community participation is a tangible manifestation of active citizenship that reflects the responsibilities of citizens in a democratic society. Based on the theories of active citizenship and democratic participation, this study aims to examine the concept of community participation, identify its forms and typologies, and analyze its application in the context of governance and development in Indonesia. This study uses a qualitative approach with a literature review method through content analysis of various relevant academic literature. The results show that community participation encompasses three main dimensions, namely political, social, and civic participation, which are manifested in the stages of planning, implementation, utilization of results, and evaluation of development. Although decentralization opens up broader opportunities for participation, its implementation still tends to be passive due to internal and external factors. This study concludes that strengthening community participation requires a comprehensive approach through education, empowerment, bureaucratic reform, transparency, and the use of digital technology to realize substantive democracy.